Subaltern Resistance in the Mahābhārata (शोधसुधा Shodh Sudha, 2025)
This study examines subaltern resistance in the Mahābhārata through a qualitative textual analysis of the epic, complemented by relevant secondary scholarship. Focusing on marginalized figures such as Vidura, Hiḍimbā, and Śikhaṇḍī, the research examines their experiences of hegemonic domination and the modes of resistance. Using Gramsci’s theoretical framework, the analysis reveals that these subaltern characters confront cultural hegemony imposed by dominant groups and engage in both overt and covert forms of individual resistance, rather than collective action as suggested by Gramci’s theory. By integrating subaltern inquiry with Indological perspectives, this paper advances a subtle analysis of subaltern characters in classical Indian literature and its significance for contemporary critical theory.